2015
DOI: 10.1002/phar.1616
|View full text |Cite
|
Sign up to set email alerts
|

Patient Specific Factors Influencing Adherence to INR Monitoring

Abstract: The following strategies to improve adherence to INR testing are suggested: (i) assign anticoagulation providers to work with the same patients consistently; (ii) provide formal INR reminders; (iii) avoid harsh language or lecturing patients following missed INR tests; (iv) reinforce the clinical and psychological utility of INR results; and (v) facilitate access to INR testing. Adopting these strategies into clinical practice can support the patient-clinician relationship and empower patients to be more engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Frequent testing is unavoidable in ensuring safe anticoagulation; however, the provision and setup of testing centres can be addressed. Similar issues have been raised in research elsewhere [24,25]. Capillary testing is a quick and easily applicable alternative to venous sampling.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Frequent testing is unavoidable in ensuring safe anticoagulation; however, the provision and setup of testing centres can be addressed. Similar issues have been raised in research elsewhere [24,25]. Capillary testing is a quick and easily applicable alternative to venous sampling.…”
Section: Discussionmentioning
confidence: 67%
“…Amongst those prescribed VKAs, research has demonstrated that although many patients find monitoring burdensome [22], a significant number derived confidence from monitoring, reassuring them of their control over their illness with many claiming they would be apprehensive about anticoagulants that required no such monitoring [23][24][25]. Research also shows patients rely heavily on the availability of specialist anticoagulation staff to manage their VKA therapy [23].…”
Section: Introductionmentioning
confidence: 99%
“…In our case, a poor adherence to anticoagulant therapy may have contributed to the adverse event; therefore, counseling with our hospital's staff was provided and discharge INR was 2.7. Strategies to improve anticoagulant adherence and INR monitoring include formal INR monitoring reminders (both written, by telephone, or text-messages), avoiding harsh language during patient encounter, the reinforcement of the utility of INR results, and to facilitate access to INR testing [8].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we could not evaluate other socioeconomic factors with known impact on anticoagulation quality and outcomes, such as patient income and living area [ 23 , 44 , 47 49 ]. However, Swiss residents have universal health care coverage and a good access to health care, including anticoagulant drugs and monitoring [ 50 ]. Moreover, there was no relationship between income class and access/affordability of vitamin K antagonists in an international study [ 51 ].…”
Section: Discussionmentioning
confidence: 99%